Sosialisasi Dan Edukasi Virtual "DAGUSIBU" Guna Meningkatkan Pengetahuan Tentang Obat dan Alat Kesehatan Yang Baik dan Tepat Di Sungai Panas, Bengkong, Batam - Suhaera, Suhaera; Sri rachmayanti, Aprilya; Sammulia, Suci Fitriani; Haryani , Reny; Meilanda, Rastria; Kamilah Idzan , Nur; Santika, Rini (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Science and technology in the field of the drug industry are advancing along with the development of the disease. The existence of a health insurance program encourages the emergence of various drug dosage forms in the community. These technological advances have given the public easy access to information, for example, about medication. Hard drugs, psychotropics, and narcotics can be obtained at pharmacies with a doctor's prescription, while limited over-the-counter drugs can be obtained at licensed pharmacies and drugstores. The outreach method used in this service, which is carried out online with the existence of socialization and education activities through the virtual Chinsibu, can be useful and can apply directly to the family and around the Dagusibu. The conclusion obtained from this service is that many residents get DAGUSIBU information.